KARAKTERISTIK MOLEKULER DAN FILOGENI LALAT BUAH Bactrocera occipitalis (Diptera:Tephritidae) DARI TARAKAN BERDASARKAN SEKUEN NUKLEOTIDA GEN COI - Martiningsia, Dwi; Wijaya, I Nyoman; Sudiarta, I Putu (Journal of Agricultural Science and Biotechnology, 2017)
Bactrocera occipitalis is one species of group B. dorsalis complex. The main host of B. occipitalis is mango (Mangifera indica), guava (Psidium guajava), orange (Citrus sp), sapodilla (Achras zapota) and star fruit (carambola Averrhoa). Region of distribution B. occipitalis are Philippines, East Malaysia (Sabah), Brunei, Indonesia (Kalimantan). B. dorsalis complex has similar morphological and have a less distinctive character for taxonomic identification at immature life stages, it will be an obstacle for the export of fruit and vegetables from Indonesia related to quarantine the country of destination, and DNA-based barcode can solve this problem. Molecular Identification B. occipitalis Tarakan successfully amplified at 642 bp with COI gene. Based on sequence homology COI B. occipitalis Tarakan has a high of similarity with B. occipitalis Philippines is 99.4% -100%. The phylogenetic analysis of DNA sequences and genetic distance based on COI gene sequences showing too genetic closeness with B. occipitalis Philippines.